Development of culture-based budi pekerti learning strategies and learning styles in skills lessons - Amal, Bakhrul Khair; Farihah, Farihah; Ampera, Dina; Supsiloani, Supsiloani; Alhudawi, Usman (Indonesian Institute for Counseling, Education and Theraphy (IICET), 2023)
The purpose of this research is to develop character learning strategies, find out the learning outcomes of skills taught with hobbyist Batak culture learning strategies and Javanese culture-based learning strategies, find out the learning outcomes of skills that have visual and kinesthetic learning styles, and know the interactions between learning strategies and styles. Learning that has an impact on learning outcomes. This research is development research with a quasi-experimental treatment. The instruments used are learning achievement tests and learning style questionnaire sheets. The hypothesis was tested using Anava. The results of the study stated that learning Skills I in the Batak culture-based learning strategy class had higher learning outcomes than the Skills class with Javanese culture-based character learning strategies in 27 public schools in Medan City. Second Learning Objectives Student skills have a higher kinesthetic learning style compared to students who have a visual learning style in Medan City Middle School students. So for culture-based learning strategies, the results will be better if students have a tendency for kinesthetic learning styles, because kinesthetic learning styles are in accordance with character learning strategies.